Children's Acquisition of Arabic Language Based On Chomsky's Theory Of Nativism - Massofia, Fitrah Dinanti; Suci Ramadhanti Febriani; Budianto, Langgeng (Institut Agama Islam Negeri Palangka Raya, 2024)
This study delves into the acquisition of Arabic language by children in the context of Chomsky's Theory. Acquisition of Arabic language for non-native students in Indonesia is very important to find out how Indonesians acquire arabic language and are able to understand the rules of the target language. The research focuses on non-native students in Indonesia, shedding light on how they grasp Arabic language and comprehend its linguistic rules. Through a qualitative approach and the Miles and Huberman model for data analysis, the study reveals that children can proficiently learn Arabic through language acquisition rather than traditional learning methods. And results of study are that children can master arabic language by means of language acquisition, if he masters the second language it is not through the learning process in school. The findings underscore the significance of innate language skills in children, as proposed by Chomsky's Theory of Nativism, emphasizing the presence of a Language Acquisition Device (LAD) from birth. This study contributes valuable insights into the natural language acquisition process and the role of innate linguistic abilities in mastering Arabic language skills. So, there must be some important aspects regarding the language system that is naturally within the child.